Transparansi dan akuntabilitas dana desa dalam perspektif Badan Pemeriksa Keuangan Republik Indonesi (BPK RI) - Ramadhani, Alia; Amalia, Nadiva; Zulkarnain, Teuku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research discusses the authority of the Supreme Audit Agency (BPK) in examining village funds sourced from the State Budget (APBN) and its function towards the agricultural sector. Based on Law No. 15/2006, BPK is responsible for ensuring transparency and accountability in village financial management. BPK emphasizes transparency and accountability are essential in the use of village funds to prevent misuse and allow the community to be involved in supervision, which has a positive impact on village development, including the agricultural sector. The research method uses a normative approach with legal analysis to evaluate the implementation of BPK's authority at the village level. The results show that the level of transparency in the management of village funds varies in each village. Some villages have implemented good information systems, such as periodic publication of financial reports including the use of information.